2014
DOI: 10.1093/geronb/gbu142
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Age to Personal Network Size, Relational Multiplexity, and Proximity to Alters in the Western United States

Abstract: Although personal network size ultimately declines with age, we find that increases for some relations extend well into late-midlife and most elders still maintain numerous contacts across diverse relations. The evidence we present suggests that older people tap into an wider variety of different network members for different types of relations than do younger people. This is true even for populations in rural settings, for whom immediate access to potential alters is more limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 36 publications
(36 reference statements)
4
26
1
Order By: Relevance
“…Contrary to the suggestion that older PLWHA face increased risk of isolation (Shippy & Karpiak, 2005), loneliness (Emlet, 2006;Karpiak et al, 2006) and lack of appropriate support (Schrimshaw & Siegel, 2003), we found that the social networks of participants to be large, strong, and supportive, consistent with findings for the general population (Smith et al, 2015). After being infected, they established new acquaintanceships and adopted new ways of viewing life.…”
Section: Discussionsupporting
confidence: 73%
“…Contrary to the suggestion that older PLWHA face increased risk of isolation (Shippy & Karpiak, 2005), loneliness (Emlet, 2006;Karpiak et al, 2006) and lack of appropriate support (Schrimshaw & Siegel, 2003), we found that the social networks of participants to be large, strong, and supportive, consistent with findings for the general population (Smith et al, 2015). After being infected, they established new acquaintanceships and adopted new ways of viewing life.…”
Section: Discussionsupporting
confidence: 73%
“…Comparisons of the demographic composition of the sample with Census data of these locations show good overall agreement (for more extensive details on data collection see Butts et al 2014 andSmith et al 2014 7…”
Section: Methodsmentioning
confidence: 72%
“…core ties for discussing important matters, which we expect to be less spatially compact compared to socializing ties, and 3.) kin ties, whose spatial patterning is most uncertain (see Boessen et al, 2014;Smith et al, 2014;Fischer, 1982;Freeman, 2001 for examples using these relationships). Before turning to the methods, we briefly review the literature on the built environment and social networks.…”
Section: Do Land Uses Matter For Personal Network Structure?mentioning
confidence: 99%
“…First, the main source of data comes from a large-scale egocentric network study that contains spatial locations of both egos and alters: the American Social Fabric Project (ASFP). The AFSP contains a population sample of Los Angeles, a population sample of the two communities in Southern California, a spatially stratified sample of Southern California, and a spatially stratified sample of the Western United States (for more extensive details on data collection see Butts et al 2014 13 andSmith et al 2014). We use data from the Southern California respondents to test our research questions for this study in part because we are able to link these data with micro crime data in neighborhoods (N = 1,359).…”
Section: Methodsmentioning
confidence: 99%